Diversity characteristics of arbuscular mycorrhizal fungi communities in the soil along successional altitudes of Helan Mountain, arid, and semi-arid regions of China - Yan, Peixuan; Hou, Hui; Lv, Yingze; Zhang, Haiying; Li, Jia; Shao, Leilei; Xie, Qinmi; Liang, Yongliang; Li, Jingyao; Ni, Xilu (Frontiers in Microbiology, 2023)
Arbuscular mycorrhizal fungi (AMF) perform a vital role in terrestrial ecosystems. To investigate the diversity of AMF communities on the western slope of Helan Mountain at different altitudes and their influence factors, high- throughput sequencing was used to study the structure and diversity of soil AMF communities under different environments and their interrelationships between AMF and environmental factors. The results revealed that there were significant differences (P<0.05) in the physical and chemical properties of the soil along the different altitudes. A total of 1145 OTUs were obtained by high-throughput sequencing, belonging to 1 phylum, 4 class, 6 orders, 13 families, 18 genera and 135 species, with the dominant genus being Glomus, which accounted for 75.27% of the relative abundance of the community. Soil AMF community structure was shown to be variable at the generic level according to NMDS analysis. Correlation analysis showed that soil pH, water content (WC), organic matter (OM), available K, available P and N were significantly correlated with AMF community diversity and species abundance (P<0.05, P<0.01). Based on redundancy analysis (RDA) and Monte Carlo test results, soil pH, WC and OM had highly significant effects (P<0.01) on AMF community diversity and species abundance. This study investigates the relationship between AMF community structure and diversity and soil physicochemical properties at different elevations on the western slope of Helan Mountain, which is of great significance to the study of the Helan Mountain ecosystem.